Cork and metals: a review (Wood Science and Technology, 2009)
All published results available regarding ash content and 21 chemical elements were chronologically compiled. The evolution of analytical methodologies, the rising interest in the knowledge of certain elements at a certain time, and the relation between concentrations and time, are among the gathered information within a period of 221 years, starting with the ﬁrst published study from the year 1787. Rather than establish a correlation between the inorganic content of cork and its quality, the aim of this data collection is to remove all doubts regarding what is already known on the inorganic content of cork.

Cork and metals: a review - C. C. da Ponte-e-Sousa, João Carlos a; Neto-Vaz, António Manuel; de C. C. da Ponte-e-Sousa, João Carlos a; Neto-Vaz, António Manuel (Wood Science and Technology, 2009)
All published results available regarding ash content and 21 chemical elements were chronologically compiled. The evolution of analytical methodologies, the rising interest in the knowledge of certain elements at a certain time, and the relation between concentrations and time, are among the gathered information within a period of 221 years, starting with the ﬁrst published study from the year 1787. Rather than establish a correlation between the inorganic content of cork and its quality, the aim of this data collection is to remove all doubts regarding what is already known on the inorganic content of cork.
Keywords: ash content; cork (voyant); metals; mineral elements